2000
DOI: 10.1001/archinte.160.4.470
|View full text |Cite
|
Sign up to set email alerts
|

Oral Anticoagulation Treatment in the Elderly

Abstract: A nonsignificant trend was noted toward a higher rate of both bleeding and thrombotic complications in elderly vs matched younger patients. Intracranial bleeding and fatal thrombotic events were significantly more frequent in the elderly. Our results also indicate that lower than 2.0 INRs do not preclude bleeding in the elderly nor offer adequate protection from thrombotic events. Moderate anticoagulation (2.0-3.0 INRs) in elderly patients seems the safest and most effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(27 citation statements)
references
References 25 publications
3
20
0
2
Order By: Relevance
“…In our study the rate of bleeding events was not affected by age in agreement with some studies [21][22][23][24], whereas other studies reported an increased incidence of bleeding in the elderly [1,9,25,26]. As the indication for OAT in patients older than 75 years is growing wider, our finding of no increase in the risk of bleeding is of clinical relevance for the evaluation of the benefit/risk ratio of OAT in the elderly.…”
Section: Discussionsupporting
confidence: 91%
“…In our study the rate of bleeding events was not affected by age in agreement with some studies [21][22][23][24], whereas other studies reported an increased incidence of bleeding in the elderly [1,9,25,26]. As the indication for OAT in patients older than 75 years is growing wider, our finding of no increase in the risk of bleeding is of clinical relevance for the evaluation of the benefit/risk ratio of OAT in the elderly.…”
Section: Discussionsupporting
confidence: 91%
“…Resultados similares foram encontrados por Poli et al 17 , estudando um número maior de pacientes. Trabalhos antigos da literatura já indicavam essa falta de relação entre sangramento e sexo [49][50][51] ; outros, entretanto, indicam uma freqüência maior de hemorragias nas mulheres em uso dos AVK 37,52 .…”
Section: Discussionunclassified
“…Umgekehrt kann aber auch eine insuffiziente Antikoagulation das sekundäre Thromboembolierisiko statistisch signifikant erhöhen [1]. Medikamenteninteraktionen spielen in diesem Zusammenhang eine wesentliche Triggerfunktion.…”
Section: Schlussfolgerungenunclassified